2015
DOI: 10.3389/fenrg.2014.00063
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Based Catalysts: Chemical Fixation of CO2 with Epoxides Leading to Cyclic Organic Carbonates

Abstract: As a C1 feedstock, CO 2 has the potential to be uniquely highly economical in both a chemical and a financial sense. In particular, the highly atom-economical acid-catalyzed cycloaddition of CO 2 to epoxides to yield cyclic organic carbonates (OCs), a functionality having many important industrial applications, is an attractive reaction for the utilization of CO 2 as a chemical feedstock. Metal-organic frameworks (MOFs) are promising candidates in catalysis as they are a class of crystalline, porous, and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
163
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(167 citation statements)
references
References 63 publications
0
163
0
4
Order By: Relevance
“…As mentioned earlier, the most effective catalysts have both Lewis acid and Lewis base sites. For example, previous studies have shown that catalysts such as zeolites or mesoporous silicate with acid–base pairs are more active . The catalytic sites of MOFs for the CO 2 /epoxides coupling reaction may be the nodes/secondary building units (SBU), the functional linkers, or both .…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned earlier, the most effective catalysts have both Lewis acid and Lewis base sites. For example, previous studies have shown that catalysts such as zeolites or mesoporous silicate with acid–base pairs are more active . The catalytic sites of MOFs for the CO 2 /epoxides coupling reaction may be the nodes/secondary building units (SBU), the functional linkers, or both .…”
Section: Resultsmentioning
confidence: 99%
“…MOFs combine the benefits of both heterogeneous and homogeneous catalysis [35]. It is possible to prepare MOFs in which the catalytic functions are efficient at their three major components: the metal nodes, the organic linker, and the porous system.…”
Section: Metal-organic Frameworkmentioning
confidence: 99%
“…Constituindo-se como a forma mais oxidada do carbono, o CO2 apresenta natureza inerte, dessa forma, a síntese de carbonatos cíclicos via cicloadição necessita do uso de catalisadores (Zalomaeva et al, 2013;Beyzavi et al, 2015;Kim et al, 2013). De modo a evitar o inconveniente da separação dos catalisadores homogêneos convencionais, diversos catalisadores heterogêneos têm sido investigados, dentre eles, os materiais que compõem a classe das Metal-Organic Frameworks (MOFs) (Zalomaeva et al, 2013;Kim et al, 2013).…”
Section: Ufscar -São Carlos -Sp 16 a 19 De Julho De 2017unclassified
“…Muito importante na escolha da MOF é verificar a presença de sítios ácidos ou básicos na estrutura (Beyzavi et al, 2015;Kim et al, 2013). Em seus trabalhos, J.…”
Section: Ufscar -São Carlos -Sp 16 a 19 De Julho De 2017unclassified
See 1 more Smart Citation